Evidence that variations in pretraining hydration status are related to the frequency of endurance training in elite adolescent sprinters - Campbell, E. H.; Irving, R.; McFarlane, S.; Dilworth, L.; Poudevigne, M.; Bailey, J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Although the effect of dehydration on performance is widely studied, limited data concerning the levels of risk training types pose to hydration status exists. This study sought to determine: 1) pretraining hydration status in adolescent sprinters relative to non-athletes; 2) changes in hydration markers across a season of adolescent sprinters relative to non-athletes; and 3) if frequency of training type explains unique variance in hydration. METHODS: Hydration (via pretraining urine osmolality [UOsm] and thirst perception [TP]), daily water intake (TWI) (via 24-h food/fluid diaries) and frequencies of resistance, endurance and sprint training types (via training regime questionnaires) were assessed in 26 sprinters (age: 15.6±1.9 years) and 26 non-athletes (age: 16.0±1.6 years), during 4 mesocycles (general [T1] and specific [T2] preparation; precompetitive [T3] and peaking [T4] phases), over 26 weeks. RESULTS: Most athletes (62-81%) and non-athletes (73-92%) were underhydrated (UOsm>700 mOsmol/kg) pretraining across the season, despite a low TP. There were significant time (P=0.042) and group (P=0.006) effects, and a main group by time interaction for UOsm (P=0.006) but not TP across the season, after controlling for TWI. Greater UOsm (in mOsmol/kg) were observed during T1 (906.3±250.1) and T2 (934.5±257.0) compared to T3 (852.1±268.8) and T4 (854.2±218.8). There was no significant change across the season for non-athletes. Frequencies of endurance training were positively associated with UOsm and explained unique variances across the season (R2 range from 7%-16%). CONCLUSIONS: Underhydration is high in the adolescent population. Training type may be related to the variations in hydration throughout a season, which may help to inform hydration practices of sprint athletes.